EVALUATION OF GEOTHERMAL RESERVOIR CONDITIONS BASED ON WELL PADS GEOCHEMICAL DATA IN LX GEOTHERMAL FIELD - Monica Megita Veronika Assa; Dianto Isnawan (KURVATEK, 2022)
The research was conducted at the Geothermal Company Energy Lx Area. The research area includes three well pads of geothermal power plants, namely X1, X2, and X3, which are stratigraphically composed of quaternary volcanic rocks. Based on the geochemical data of the well pad, it shows that the chloride type fluid is in equilibrium/partial equilibrium with the reservoir temperature in the range of 230 – 300°C from the silica and Na-K geothermometer analysis. The geothermal system in the research area is a hydrothermal magmatic system with two-phase fluid dominated by water. Evaluation of reservoir conditions from monitoring the X3 well pad shows a decrease in temperature for the last 3 years from 320°C in 2018 to 290°C in 2020. Graphical analysis of several chemical elements including Ca, Cl, SiO2, Boron and HCO3 shows a trend with the same pattern on several elements/compounds so it can interpret that there are no mixing process occurs in the reservoir, especially mixing with drill pipe wall cement or groundwater. Utilization of two-phase geothermal fluid in the Lx Geothermal Field produces electricity with a capacity reaches more than 100 MW and is still being developed in several areas that are currently in the geothermal geochemical exploration stage.